Revisiting the LiPON/Li thin film as a bifunctional interlayer for NASICON solid electrolyte-based lithium metal batteries - Lee, Seung hwan; Jung Se Hun; Yang, Sungeun; Lee, Jong-Ho; Shin, Hyunjung; Kim, Joosun; Park, Sang baek (Elsevier BV, 2022)
Emerging solid-state lithium batteries demand a stable solid electrolyte against both Li anodes and high-voltage cathodes. The NASICON-type Li1.5Al0.5Ge1.5(PO4)3 (LAGP) solid electrolyte is highly tolerant to high-voltage operation and air environments, but it suffers from poor interfacial compatibility with Li anodes. Herein, we revisit the Li/LiPON bilayer thin-film in mature and ultrastable thin-film batteries as a bifunctional interlayer that can resolve both chemical and mechanical interfacial problems between Li anodes and LAGP. Interestingly, defect-free contact of the Li thin film onto LiPON/LAGP dramatically reduces the anode interface impedance between LAGP and Li foil, which eliminates the step for Li foil heating. As a result, it delivers a high capacity and rate capability with a long cycle in all-solid-state Li-O2 batteries. Moreover, by virtue of a systematic thin-film configuration, a model study with different interlayer combinations as well as LiPON thicknesses clearly distinguishes two degradation mechanisms in LAGP-based cells: chemical reduction of Ge at the anode interface and mechanical contact loss by nonuniform Li stripping/plating upon cycling. Thanks to its exceptional electrochemical stability window, this Li/LiPON-modified LAGP will help to achieve the commercialization of safe and long-lasting solid-state lithium batteries. ？ 2022 Elsevier B.V.